TRANSLATION TECHNIQUES IN INDONESIAN TRANSLATION OF MONOLOGUE IN LOVE, SIMON MOVIE - Wida Wardoyo; Mochamad Rizqi Adhi Pratama (Universitas Ngudi Waluyo, 2022)
This is a study which analyzes translation techniques used by the translator in the monologue of Love, Simon movie. The purpose of the study is to explain the translation techniques and to determine the most dominant translation technique used in translating monologue in Love, Simon movie. This study is classified into descriptive qualitative research. In the study, the writer collectted and analyzed the data to get a conclusion. The data were gained by watching the movie, documenting the script, selecting, identifying, classifying, counting, and conclusion. The writer used the translation techniques introduced by Molina and Albir (2002) to analyze and classify the data. There are 12 techniques found in 225 data. They are adaptation, amplification, borrowing, calque, compensation, established equivalent, generalization, linguistic compression, literal, modulation, reduction, and variation. The most dominant translation technique is established equivalent which occurs 77 times and it represents 34,22%.Â Kata Kunci: translation technique, movie, monologue, subtitle, Love Simon, descriptive qualitative